2015
DOI: 10.1371/journal.pone.0123117
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review on Health Resilience to Economic Crises

Abstract: BackgroundThe health effects of recent economic crises differ markedly by population group. The objective of this systematic review is to examine evidence from longitudinal studies on factors influencing resilience for any health outcome or health behaviour among the general population living in countries exposed to financial crises.MethodsWe systematically reviewed studies from six electronic databases (EMBASE, Global Health, MEDLINE, PsycINFO, Scopus, Web of Science) which used quantitative longitudinal stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
80
1
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(92 citation statements)
references
References 47 publications
(202 reference statements)
4
80
1
7
Order By: Relevance
“…The rating for each component ranges from 1 (low risk of bias; high methodological quality) to 3 (high risk of bias; low methodological quality). Thus, the papers selected were attributed a global rating, according to the component ratings, of WEAK, MODERATE, or STRONG, based on the following criteria: STRONG was attributed for studies with no “weak” ratings and at least three “moderate” ratings; MODERATE was attributed for those with one “weak” rating or at least three “strong” ratings; and WEAK was attributed to papers with two or more “weak” ratings (Stroup et al ., ; Glonti et al ., ).…”
Section: Methodsmentioning
confidence: 97%
“…The rating for each component ranges from 1 (low risk of bias; high methodological quality) to 3 (high risk of bias; low methodological quality). Thus, the papers selected were attributed a global rating, according to the component ratings, of WEAK, MODERATE, or STRONG, based on the following criteria: STRONG was attributed for studies with no “weak” ratings and at least three “moderate” ratings; MODERATE was attributed for those with one “weak” rating or at least three “strong” ratings; and WEAK was attributed to papers with two or more “weak” ratings (Stroup et al ., ; Glonti et al ., ).…”
Section: Methodsmentioning
confidence: 97%
“…Recession-related hardships may also amplify the negative health consequences of low educational attainment and possibly worsen social inequalities in health. In a review of prior recession findings (see Glonti et al, 2015), low educational attainment was more strongly associated with negative health outcomes during periods of economic downturns compared to before their onset. Additionally, Cutler et al, (2015) demonstrated that periods of high unemployment amplified the negative health consequences of low educational attainment.…”
Section: Pre-existing Vulnerability To the Great Recession: Low Educamentioning
confidence: 99%
“…Moreover, economic recession tends to widen the social divide between people affected by mental illness and general population [812]. As a matter of fact, large-scale population studies reported that “unemployment” was strongly associated with a deterioration of mental health scores [13, 14]. …”
Section: Introductionmentioning
confidence: 99%